Implementasi Literasi Digital Dalam Peningkatan Pemahaman Karakter Keagamaan Siswa - Mulyadi, Veri Ikra (Journal of Islamic Education and Learning, 2024)
This study aims to examine the implementation of digital literacy in an effort to improve students' understanding of religious character through the library study method. The background of this study is based on the challenges of the digital era which have a significant impact on character values, including religious character in students. Digital literacy, as the ability to understand and utilize information through digital media wisely, is a potential means in character education. This study uses a descriptive qualitative approach with a library study method, namely collecting, analyzing, and synthesizing various library sources in the form of scientific journals, books, and relevant articles in the last five years. The results of the study show that digital literacy can be a bridge in conveying religious values ??contextually and attractively to students, especially through digital platforms such as educational videos, learning applications, and social media that are directed at religious content. In addition, digital literacy also helps students distinguish valid religious information and avoid negative content. Improving understanding of religious character through digital literacy requires the active role of teachers and educational institutions in guiding students to use technology ethically and responsibly. In conclusion, digital literacy is a relevant and effective strategy in instilling and strengthening students' religious character amidst technological developments. Recommendations from this study emphasize the importance of integrating digital literacy into the religious education curriculum as well as training for teachers in the use of digital media based on spiritual values.